Interaction volume of electron beam in carbon nanomaterials: A molecular dynamics study. Issue 1700 (2014) - Yasuda, Masaaki; Wakuda, Shinya; Asayama, Yoshiki; Kawata, Hiroaki; Hirai, Yoshihiko
ABSTRACT: A molecular dynamics (MD) simulation was performed to study the interaction volume of electron beam in carbon nanomaterials. The interaction between incident electron and carbon atom in the target materials during electron irradiation is introduced by the relativistic binary collision theory. The motion of each atom in the material under electron irradiation is calculated with the MD simulation. The primary energy dependence of the interaction volume in the carbon nanotube and the multi-layered graphene are studied. The secondary damages caused by the knock-on atoms are also discussed.